2021
DOI: 10.1080/22221751.2021.2004866
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 mRNA vaccine BNT162b2 triggers a consistent cross-variant humoral and cellular response

Abstract: As the SARS-CoV-2 pandemic continues to rage worldwide, the emergence of numerous variants of concern (VOC) represents a challenge for the vaccinal protective efficacy and the reliability of commercially available high-throughput immunoassays. Our study demonstrates the administration of two doses of the BNT162b2 vaccine that elicited a robust SARS-CoV-2-specific immune response which was assessed up to 3 months after full vaccination in a cohort of 37 health care workers (HCWs). SARS-CoV-2-specific antibody r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 26 publications
5
15
1
Order By: Relevance
“…Zani et al reported that the B.1.1.7 lineage (and B.1.525 lineage) bearing the N501Y single mutation in the RBD was robustly neutralized by vaccine-elicited antibodies from naïve subjects, whereas neutralization of the B.351 and P.1 lineages was lower compared to that of the B.1 lineage, although robust [ 14 ]. Different from our data, a similar neutralizing response against the B.1, B.1.1.7, and P.1 (and B.1.525) lineages has been reported in BNT162b2-vaccinated healthcare workers, while the B.1.351 and B.1.617.2 lineages showed a consistent partial immune evasion [ 15 ]. However, we cannot exclude that this discrepancy might rely on the different neutralization assays employed, i.e.…”
Section: Discussioncontrasting
confidence: 83%
“…Zani et al reported that the B.1.1.7 lineage (and B.1.525 lineage) bearing the N501Y single mutation in the RBD was robustly neutralized by vaccine-elicited antibodies from naïve subjects, whereas neutralization of the B.351 and P.1 lineages was lower compared to that of the B.1 lineage, although robust [ 14 ]. Different from our data, a similar neutralizing response against the B.1, B.1.1.7, and P.1 (and B.1.525) lineages has been reported in BNT162b2-vaccinated healthcare workers, while the B.1.351 and B.1.617.2 lineages showed a consistent partial immune evasion [ 15 ]. However, we cannot exclude that this discrepancy might rely on the different neutralization assays employed, i.e.…”
Section: Discussioncontrasting
confidence: 83%
“…Our results show that 80% of the women who became infected during pregnancy developed a specific antibody response, consistently with what previously reported for the general population ( 27 , 28 ). In the analyzed cohort, the antibody titer peaked between week 2 and 4, and it was maintained up to week 24, consistently with how observed in the non-pregnant population ( 29 , 30 ). Although the lower number of collected samples due to some discontinuity during the follow-up, the neutralization titer significantly correlated with the IgG antibody titer, which is expected but not granted ( 31 ).…”
Section: Discussionsupporting
confidence: 84%
“…The presence of nAb is enough to completely abrogate viral infectivity per se ( 27 ). Typically, moderate-to-severe patients develop a high titer of specific antibodies, but it does not correlate with SARS-CoV-2 viral load nor it is predictive of the outcome of the disease ( 28 , 30 ). Moreover, asymptomatic or pauci-symptomatic patients might not develop specific antibodies not nAb at all, indicating the importance of other mechanisms of immune control, probably T cell-based ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…We were intrigued by our findings of comparable neutralization capacities against the Wuhan-Hu-1 and Delta peptides combined with very strong correlations between both, independent of whether antibodies resulted from a homologous or heterologous primeboost regimen. As we employed surrogate virus neutralization assays with RBD peptides only, our findings suggest that mutations besides the Delta-specific L452R and T478K are responsible for the loss of neutralization described in conventional virus neutralization tests [22,23]. Moreover, our findings attribute a reduced vaccine effectiveness against Delta not only to the loss of susceptibility against neutralizing antibodies but also to an altered T cell reactivity and/or increased viral transmission [11,24,25].…”
Section: Discussionmentioning
confidence: 67%